1995
DOI: 10.1002/app.1995.070580106
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenological description of strain rate and temperature‐dependent yield stress of PMMA

Abstract: SYNOPSISA constitutive equation to describe the yield behavior of poly(methy1 methacrylate) (PMMA) is useful not only from the technological point of view, but also for the comprehension of the nonlinear mechanisms acting in the material. In both compression and tension, the yield stress is usually represented as a function of the strain rate at different temperatures. In PMMA and other glassy polymers these curves are related by scaling, that is, they can be matched to form a master curve. Particularly in PMM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 23 publications
3
27
0
3
Order By: Relevance
“…(2)) through transient dip experiments, Brooks et al only needed to consider a horizontal shift [17]. While Povolo and co-workers studied directly the yield stress and showed that the horizontal and vertical shifts are respectively related to the characteristic strain rate _ 3 Ã and to the internal stress s i [15,16]. This later result was found after a very lengthy reasoning method.…”
Section: Strain Rate/temperature Superposition Principlementioning
confidence: 91%
See 1 more Smart Citation
“…(2)) through transient dip experiments, Brooks et al only needed to consider a horizontal shift [17]. While Povolo and co-workers studied directly the yield stress and showed that the horizontal and vertical shifts are respectively related to the characteristic strain rate _ 3 Ã and to the internal stress s i [15,16]. This later result was found after a very lengthy reasoning method.…”
Section: Strain Rate/temperature Superposition Principlementioning
confidence: 91%
“…Within the past 10 years, it has been shown, for amorphous polymers by Povolo and co-workers [15,16] and for semi-crystalline polymers by Brooks et al [17], that the two Eyring processes acting in parallel for the description of the yield stress on a wide range of temperatures and strain rates can be substituted with the cooperative model of Fotheringham and Cherry [18,19]. In line with these previous studies, we propose a new formulation of the cooperative model for amorphous polymers with the assumption that yield stress must obey the strain rate/temperature superposition principle of Bauwens-Crowet et al [7].…”
Section: Introductionmentioning
confidence: 96%
“…Concerning the internal stress, Povolo and Hermida (Povolo and Hermida, 1995;Povolo et al, 1996) proposed a linear dependence of the internal stress with temperature, but they do not have a physical model that can explain it. Nonetheless, we believe that the linear dependence of r i can find some justification in the work of Rault (1998).…”
Section: Physical Nature Of the Modelmentioning
confidence: 98%
“…Originally, Cherry (1976, 1978), and Povolo and co-workers (Povolo and Hermida, 1995;Povolo et al, 1996) have not provided any information on the nature of the activation energy of the cooperative model. It is quite remarkable to notice that the b process is also involved in the cooperative process, since it is a physical process that has been identified as a plasticity precursor.…”
Section: Physical Nature Of the Modelmentioning
confidence: 98%
See 1 more Smart Citation